Certain Class of P-Valent Analytic Function Associated with Derivative Operator and Their Properties (Contemporary Mathematics, 2024)
This study aims to define a new subclass of multivalent analytic functions in the open unit disk. Jackson's derivative operator has been used to generate this subclass. Before getting coefficient characterization, we look at certain needs for the functions related to this subclass. We can see several fascinating features, including coefficient estimates, growth and distortion theorem, extreme points, and the radius of starlikeness and convexity of functions belonging to the subclass are shown using this technique.
Keywords: new subclass; p-valent function; quantum or (i, j)-calculus; (i, j)-derivative operator